Disruptive innovation and emerging technologies for business excellence in the service sector - Singh, Malini; Tyagi, Pankaj Kumar; Nadda, Vipin; Tyagi, Priyanka (IGI Global, 2021)
"The book provides an in-depth understanding of various dimensions of scope of disruptive business innovation, to help readers understand the contributions and implications of disruptive technology, and aid in trend forecasting, design thinking and its applications, and the role of data mining & predictive analysis in today's business world."